Effect of pasteurized egg yolk on the quality of cryopreserved boar semen. Issue 8 (3rd July 2021) - Selige, Christin; Quirino, Monike; Schröter, Filip; Aepli, Matteo; Schulze, Martin
Abstract: Egg yolk (EY, control) is an essential ingredient of diluents for boar semen cryopreservation. Pasteurized egg yolk (PEY) reduces hygienic risks in processing and is easier to standardize. The aim of this study was to evaluate the in vitro effect of PEY (treatment) on frozen‐thawed boar semen. In a split‐sample approach ( n = 13 boars), it could be shown that there is neither an influence ( p > .05) on post‐thawing motility (PTM: 5, 30 and 120 min) nor on morphologically intact sperm, percentage of acrosome defects and membrane fluidity using a PEY extender compared to the control. Mitochondrial activity ( p = .043), membrane integrity ( p = .015) and PTM 300 min ( p = .023) were slightly affected in the treatment group. Overall, sperm quality was at a high level in both experimental groups. Further studies are needed to determine the impact of PEY on the fertilizing capacity of boar ejaculates.